BUSINESS STRATEGIES THROUGH FIT MANAGEMENT OF HUMAN CAPITAL AS COMPETITIVE ADVANTAGE - Haeryip Sihombing; Adi Saptari; Mohd Yuhazri bin Yaakob (Journal of Indonesian Economy and Business (JIEB), 2010)
Many organizations fail to interpret what the competitive advantages of their business. Based on lean philosophy about waste, one of the reasons is to unlock (by understandingand take advantages) of their employee’s potential. This paper proposes a conceptual framework of the so-called ‘Fitted Management’. The concept discusses two issues i.e. 1)‘Fitted Management’, an integrated concept of performance challenges, performance measurement and performance management combined with the vision and missions intocompetitive management; 2) ‘Human Transformation’, a conceptual model to support the first concept. It discusses the processing of exploring human capabilities (in organization)and how to manage this (to fit with the organization) as well as business competition in dynamic market and business climates.Keywords: human capital, competitive advantage, lean, performances, fitted management.